Assessment ASSESSMENT OF RAIN WATER HARVESTING SYSTEM - Syed Adnan Shah; Dr Mujahid Khan; Ikramullah Qayuum; Malik Ashar (Sir Syed University Research Journal of Engineering and Technology)
The life of the inhabitants of the globe is greatly dependant on water. Providing portable water to communities is of prime interest. Scarcity of water is a threat in near future in Pakistan. There is a need to search for alternate sources of water to fulfil the community requirement. Rainwater Harvesting (RWH) system is a better alternative.  Keeping in view the vast application of this system, it is adopted as an alternative source of water in a village of Abbottabad city where there is scarcity of water.  According to Public Health Engineering Department (PHED), the currently available gravity system and three tube wells are not sufficient to supply water to all the population. For this study, first, the rainfall data is collected and then by using the principle of rainwater harvesting system, the quantity of available water is calculated. The calculations were made using SCS curve number method using mean monthly rainfall depth. From calculation, we found that not only for current population but for population in 2028 can also be served by storing the water that we get from Rainwater Harvesting system if stored in a reservoir. But after 20 years i.e. in 2038, there will be deficiency of 146, 449 gallons per day of water for entire community which can easily be arranged from a small tube well. Therefore, on the basis of this study, it was recommended to the PHED of Abbottabad city to store the rainwater in a reservoir so that it can be easily utilised.